Monitoring of Serological Status in Response to PPR Vaccination in the Goat Population of Parbat, Baglung and Myagdi District of Nepal - Regmi, B.; Dhakal, I.; Shah, M. K.; Pande, K. R. (Nepalese Veterinary Journal, 2019)
Peste des Petits ruminants (PPR) is a highly contagious trans-boundary animal disease associated with 100% morbidity and 80-90% mortality in goat herds. The study was carried out to assess the immune status against PPRV in unvaccinated and post vaccinated flock as well as immune response as it relates to age, sex and breed using a homologous tissue culture PPR vaccine produced by National Vaccine Production Laboratory, Kathmandu, Nepal. A total 276 blood samples were randomly collected from different regions of Parbat, Baglung and Myagdi districts with a population of 0.0189 million goats. Out of these, 214 goats were vaccinated one month earlier and 62 were unvaccinated. PPR antibody was detected by using competitive enzyme linked immunosorbent assay (c-ELISA) (ID Screen, PPR competition test kit, IDvet France). Of the unvaccinated goats, 25.8% (16/62) were sero-positive suggesting prior exposure to PPRV. In the vaccinated goats, 75.2% (161/214) were sero-positive and 2.8% (6/214) animals were doubtful, suggesting a significant proportion failed to respond to vaccination. The competition percentage (S/N%±SD) of post-immunization (49.19±32.19) were significantly (p<0.01) lower in comparison to the respective unvaccinated mean titre (75.76±35.51). There is no significant effect of age, sex or breed on the antibody titre value in PPR vaccinated animals. The sero-prevalence of PPR in unvaccinated animals suggested that these flocks are in high susceptibility to PPR outbreak and needs an implementation of control measures to reduce economic losses. Vaccination will increase the proportion of animals with a protective antibody level, however more investigation needs to be done to determine why almost one-quarter of animals failed to seroconvert to vaccination. Further detailed study is needed to find out the risk factors responsible for low prevalence of antibody against PPRV in the immunized flock.